Effect of self-efficacy and social support on medication compliance for tuberculosis patients - Mangela, Jessica Angelina; Jusman Rau, Muhammad; Arwan, Arwan; Nurul Fadjriah, Rasyika; Wayan Sridani, Ni (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Tuberculosis remains a major public health problem, and medication non-adherence continues to hinder treatment success despite the implementation of the Directly Observed Treatment Short-course (DOTS) strategy. Psychological and social factors, particularly self-efficacy and social support, play an important role in determining patients’ adherence to long-term tuberculosis treatment. This study aimed to analyze the influence of self-efficacy and social support on medication adherence among tuberculosis patients in Palu City. Research Methodology: This study employed a quantitative, comparative, analytical design with a non-experimental, cross-sectional approach. The study population consisted of 489 registered tuberculosis patients in Palu City in 2025. A total of 83 respondents were selected using probability sampling with a cluster random sampling technique from seven public health centers. Data were collected using the Morisky Medication Adherence Scale (MMAS-8), the Tuberculosis Self-Efficacy Scale (TBSES), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis included univariate analysis and bivariate analysis using independent t-tests with a significance level of p < 0.05. Results: Medical care management (p = 0.003), support seeking (p = 0.047), and psychological adjustment (p = 0.038) were significantly associated with medication adherence, whereas transmission management was not (p = 0.993). All dimensions of social support, instrumental (p = 0.031), informational (p = 0.045), appraisal (p = 0.011), and emotional support (p = 0.015), demonstrated significant associations with medication adherence. Conclusion: These findings indicate that medication adherence among tuberculosis patients is strongly influenced by both self-efficacy and social support. Strengthening patients’ confidence in managing treatment and enhancing family and social support are essential to improve adherence and treatment outcomes